The Gridded Geomagnetic Field of India with MATLAB GUI - Jayashree Bulusu; Rohit Kumar Jha; Amrita Yadav; S. P. Anand; Gopi K. Seemala; Prasant K. Tiwari; A. P. Dimri (Data Science Journal)
A unique two-dimensional gridded geomagnetic map of India is constructed using the geomagnetic field observations from 11 observatories of India, operated by the Indian Institute of Geomagnetism. In order to create the spatial grid, 11 spatial techniques are compared with observed magnetic field during 2011–2020. Out of the 11 known techniques of spatial interpolation, the Modified Shepard’s Method is selected as the best suitable method for interpolation. The spatial gird provides the hourly values of absolute and variations in horizontal (H) and vertical (Z) magnetic field over India. The spatial grid can be applied to higher temporal resolution of data sets as well. This map can be used to get the regional changes in the magnetic field during quiet and disturbed conditions. A user-friendly MATLAB based GUI is created for obtaining the spatial grid.